A prospective study to investigate circadian rhythms as health indicator in women’s aging - Deeksha Malhan; Müge Yalçin; Susanne Liedtke; Rayka Grötsch; Christina Enzmann; Monika Rau; Angela Relógio (npj Women's Health)
Abstract The circadian clock plays a crucial role in regulating the timing of numerous physiological processes. Its dysregulation has severe implications for the organism’s homeostasis and is among the main characteristics of aging. As women age and transition through menopause, disruptions in circadian rhythms may occur, leading to symptoms such as insomnia, mood changes, or altered energy levels. In this prospective non-randomized cohort study, we seek to characterize and better understand circadian clock alterations in women across various stages of their reproductive cycle, both with and without daily routine alterations (e.g., specific diet, light exposure). Understanding the intricate relationship between circadian rhythms and female health during the aging process is essential for developing targeted interventions to mitigate symptoms and promote overall well-being in menopausal women. Findings from this study will be used to devise tailored circadian rhythm assessments and interventions for women, facilitating the alleviation of menopause-related symptoms and promoting healthy aging.